Physical activity and physical fitness among children and adolescents after the onset of the COVID-19 pandemic in the WHO European Region: a systematic review protocol - Ludwig-Walz, Helena; Siemens, Waldemar; Heinisch, Sarah; Dannheim, Indra; Loss, Julika; Bujard, Martin (BMJ open, 2023)
Introduction The implementation of COVID-19 pandemic-related restrictions resulted in limitations for physical activity (PA) opportunities, which may have initiated a longer-term behavioural change. The protocol describes the methodology for a planned systematic review that aims to summarise changes in PA and physical fitness (PF) in children and adolescents in the WHO European Region after the onset of the COVID-19 pandemic. - Methods and analysis The protocol adheres to the ‘Preferred Reporting Items for Systematic Review and Meta-Analysis for Protocols’ (PRISMA-P) statement. Using a peer-reviewed search strategy according to the evidence-based checklist ‘Peer Review of Electronic Search Strategies’ (PRESS), we will perform a systematic literature search in seven databases. Inclusion criteria are all primary studies that gathered data on children and adolescents ≤19 years living in the WHO European Region and made a comparison to pre-pandemic data. Primary outcomes are PA and PF. We will assess the risk of bias with the ‘Risk of Bias Instrument for Non-Randomized Studies of Exposures’ (ROBINS-E). The ‘Grading of Recommendations Assessment, Development and Evaluation’ (GRADE) approach will be used for the evaluation of the certainty of evidence. Also, subgroup analyses will be performed (eg, for gender, age, stringency of pandemic restrictions). - Ethics and dissemination Ethical approval is not required, as primary data will not be collected in this study. The results will be presented in a peer-reviewed publication and at congresses relevant to the research field. - PROSPERO registration number CRD42023395871.
Online veröffentlicht: 20. September 2023
Gesehen am 04.01.2024